A Review on Selenium-enriched Green Tea: Fortification Methods, Biological Activities and Application Prospect - Liang, Jin; Puligundla, Pradeep; Ko, Sanghoon; Wan, Xiao-Chun (Universiti Kebangsaan Malaysia, 2014)
Selenium (Se) has been recognized as an essential nutrient for humans. Plant foods are the predominant source of selenium and majority of dietary selenium is absorbed depending on the type of food consumed. Nowadays, green tea is becoming increasingly popular for its prominent health benefits, including the ability to supplement selenium in organically bound, natural food form. The selenium content of Se-enriched green tea is influenced by the selenium level of local soils in which it is grown. However, selenium content of plants can also be improved by artificial fortification methods. In this review, the chemical speciation and biological functions of selenium, fortification methods, biological activities and nutraceutical applications of Se-enriched green tea are discussed. This review provides insights into the current research and the importance of Se-enriched green tea in the enrichment of human nutrition and health.